Irrigation schedule in producing quality basmati rice (Oryza sativa) - BALI, AMARJIT S; UPPAL, H S (The Indian Journal of Agricultural Sciences, 2013)
Schedule of irrigation application after 2 days of infiltration of ponded water produced significantly higher grainyield over that of 4 days after infiltration of ponded water. The irrigation scheduled at 2 days after infiltration of waterthough having higher water expense resulted in greater water expense efficiency. Significantly improved rice (Oryzasativa L.) recovery and protein content of polished kernels and lowering of alkali splitting score were observed underthe treatment of frequent irrigation application. With drawal of irrigation at 21 days after 50% flowering had significantlyhigher grain yield, water expense efficiency, hulled, milled and head rice recoveries and protein content ofbasmati rice than at withdrawal of irrigation at 7 or 14 days after 50% flowering.